PENGARUH PROPORSI BUAH NAGA MERAH (Hylocereus polyrhisuz) DAN BUAH SIRSAK (Annona muricata L) TERHADAP TINGKAT KESUKAAN PANELIS PADA FRUIT LEATHER - Lorensia Susanti Lamban; Jenny Kandou; Gregoria S.S. Djarkasi (Universitas Sam Ratulangi, 2017)
ABSTRACTFruits are generally susceptible to damage especially special fruits that contain high water content such as red dragon fruit and soursop fruit that required further processing in order to maintain nutrient content and prolong the shelf life. Examples of processed fruit are fruit leather. The aim of this research is to get the treatment of proportion of red dragon fruit and soursop fruit favored by panelists based on the sensory test and determine the chemical content of the resulting fruit leather. This research use Completely Randomized Design with 6 treatment of proportion ratio of red dragon fruit and soursop fruit (A = 0%: 100%), (B = 30%: 70%), (C = 40%: 60%), (D = 50%: 50%), (E = 60%: 40%), and (F = 70%: 30%). Parameters analyzed were water content, reducing sugar content, vitamin C content, and total acid. From the research result, it was found that the selected treatment based on physicochemical properties was B treatment (30%: 70%). In this treatment has a chemical content with water content of 18.39%, vitamin C levels of 52.55 Mg / 100 gr, reducing sugar content 65.32% and total acid 1.43%.Keywords: Fruit leather, red dragon, soursop